Greening of AIT : effects of aquaculture effluents on the trophic state of AIT surface water - Vu, Hoang Hoa; Lin, Chang Kwei; Hambrey, J. B.; Sununtar Setboonsarng; The Government of Denmarks (DANIDA) (Bangkok : Asian Institute of Technology, 1995)
This study was conducted at Asian Institute of Technology (AIT), located at 42 km North of downtown Bangkok. As eutrophication has become a general surface water problem, and aquaculture discharge has been proved to be an important cause of eutrophic state in many receiving water body, this study concerns the impact of AIT aquaculture effluents on trophic state of the AIT canal water. The study period was relatively short, from 05 February to 05 June 1995. Nutrient concentrations, chlorophyll a concentration and Secchi disk transparency were used as the indicators for trophic categorization in the canal. The nutrient contribution from aquaculture effluents was assessed based on different setting scenarios and present status at aquaculture field. The study showed that the average nutrient concentrations in the canal water with 5.69 mg/L nitrogen and 0.39 mg/L phosphorus were relatively high and resulted in a high phytoplankton production (53 mg Chl-a/m3), and also the highly turbid water (33 cm Secchi disk transparency). Many symptoms of eutrophication were observed, such as bad smell, changing in water color, and the abundance of rooted plants, etc. The canal falls in highly eutrophic state. Aquaculture effluents, containing an annual nutrient load to the canal of 134 kg nitrogen and 36 kg phosphorus, constitute a major source of nutrient inputs and together with other nutrient sources, accelerate eutrophic state of the canal. Important nutrient contribution of aquaculture effluents was also proved by higher values of nutrient concentrations and lower values of transparency of canal water measured near aquaculture field during the study period. From the result of setting experiment, high reduction rate of nutrient content (65% nitrogen and 82% phosphorus) in the aquaculture effluent can be achieved after 3 weeks retaining in aquaculture internal drainage canal. It is proposed that the aquaculture effluent should be kelp in the treatment canal in at least 3 weeks in order to reduce the environmental impact of the fish farming practices in aquaculture field. Long-term studies on this subject and on other measures to improve the environmental condition at AIT canal were recommended for future works
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Environment, Resources, and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1995
Keywords: Aquaculture -- Environmental aspects